2002
DOI: 10.1300/j105v27n03_01
|View full text |Cite
|
Sign up to set email alerts
|

Buy, Don't Borrow

Abstract: Downloaded by [University of Tasmania] at 16:32 13 October 2014 normal selection. The bibliographers concluded that the patron-driven Books on Demand program is a valuable complementary collection development tool. It consistently adds a very high percentage of relevant scholarly titles to the collection which provides input from patrons who do not ordinarily have a voice in collection development decisions and fills in gaps in interdisciplinary areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…However, through the implementation of access-informed collection development strategies like those discussed here, ILL has the potential to take on a more active role in collection development. Again, ILL is not just an institutional stop-gap, allowing collection managers to avoid the hard question of 34 COLLECTION MANAGEMENT how to achieve a balance between access and ownership. Instead, it is a source of valuable information about user needs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, through the implementation of access-informed collection development strategies like those discussed here, ILL has the potential to take on a more active role in collection development. Again, ILL is not just an institutional stop-gap, allowing collection managers to avoid the hard question of 34 COLLECTION MANAGEMENT how to achieve a balance between access and ownership. Instead, it is a source of valuable information about user needs.…”
Section: Resultsmentioning
confidence: 99%
“…33 Kristine Anderson reports similar outcomes for Purdue, which implemented a "Books on Demand" program in 2000. 34 Through careful review of ILL requests, selectors for these programs identified items that increased the value of their collections beyond their ownership cost. Spokespersons for these programs agree that just-in-time acquisitions helps to make the selection process more accountable to patrons' needs, tends to get materials into patrons' hands more quickly than ILL, and, because just-in-time acquisitions allows patrons to hold onto items longer, tends to increase user satisfaction.…”
Section: Just-in-time Acquisitionsmentioning
confidence: 99%
“…Patron-Driven Acquisition has become a topic of discussion at recent meetings of library associations, several articles have been recently published and a book on the subject is appearing in early 2012 [4]. Anderson et al discuss the book on demand program of the Purdue university libraries which has been operating since 2000 [5]. In this program, books requested through interlibrary loan were purchased rather than being borrowed from other libraries.…”
Section: Library Collection Development Modementioning
confidence: 99%
“…ILL staff buy books that meet preestablished criteria, such as price, publisher, and publication date; upon receipt, patrons check out the books and then return them to be added to the local library collection . The success of print-based PDA programs, as documented by studies that analyze titles purchased through such programs, eventually led to the development of PDA for e-books (Anderson et al, 2010;Bracke, 2010;Nixon & Saunders, 2010;Nixon, Ward, & Freeman, 2014;Tyler, Falci, Melvin, Epp, & Kreps, 2013). Swords (2011a) states that "PDA is the product of technology and very specifically of the coming of the age of e-books" (p. 2).…”
Section: Introduction To Patron-driven Acquisitionsmentioning
confidence: 99%